STUDY OF CONSUMER ACCEPTANCE AGAINST CATFISH (Pangasiusdjambal)MEATBALLS WITH SUBSTITUTION OF YELLOW SWEET POTATO - Rokhimin Rokhimin; Rahman Karnila; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAK  This research was aimed to determine the best amount of yellow sweet potato flour on processing of catfish (Pangasiusdjambal)meatballs. The method used in this study was the experimental method that was processing the catfish meatballs substitued with yellow sweetpotato flour. The design used was a Completely Randomized Design (CRD) non factorial with 4 treatment levels and 3 replicates. The treatment was the different concentration of yellow sweet potato with 4 treatment levels: Bo (without addition of yellow sweet potato flour/control), B1(25 g of yellow sweet potato flour), B2 (35 g of yellow sweet potato flour), and B3(50 g of yellow sweet potato flour) with 3 replicates. The parameter used in this research was organoleptic (appearance, texture, aroma, and taste) and chemical analysis (moisture, fat,protein, and ash content). Based on the result showed that B1 treatment was most preferable by consumer acceptance(98,43%) which characteristics of appearance was brown grayish colour, specific aroma of catfish meatballs, soft and chewy texture, spices flavor. The proximat analysis of moisture, fat, protein, and ash content was 73.07%, 1.59%, 14.91%, and 1.66%, respectively. Keywords: catfish meatballs, consumer acceptance, substitution